Geographies of Place in Digital Art History. Issue 1 (March 2022) - Middle, Sarah; Horne, Ryan; A. McMeekin, David; Zuanni, Chiara; Butterworth, Alex
Abstract : Art history research examines objects as embedded in a web of relationships, including multiple spatial dimensions (e.g. of the materials, of the artist, of the cultural influences, of the museum collection, and of the temporary exhibitions). However, this richness of nuances is not yet fully encompassed in Linked Open Data standards. This paper aims to examine how the multiplicity of places entangled in art objects can be represented within existing vocabularies (Getty Thesaurus of Geographic Names, Geonames, Pleiades, Trismegistos), ontologies ( CIDOC CRM, Europeana Data Model, Linked Ancient World Data, Wikidata, LIDO ) and interconnection formats (Pelagios, World Historical Gazetteer, SENESCHAL, Linked Art) . In doing so, this article raises a series of questions concerning the potential and limitation of current solutions for representing geographical information. It highlights the needs for inclusive, interoperable, open and accessible features in LOD systems in spatial humanities and it traces possible areas of inquiry for further research. The article argues that there is the need to develop more granular and comprehensive solutions for encompassing the multiplicity of places that can be enclosed in an art object, and its itineraries across time and space.